CHARACTERISTICS DISTRIBUTION MINERALOGY OF HEAVY METAL AND RARE EARTH ELEMENTS IN THE SOIL AROUND THE TAILING STORAGE FACILITY OF MIRAH KALAMANAN AREA, KATINGAN REGENCY, CENTRAL KALIMANTAN - Trias Yudhy, Calvin
The processing and refining of mining goods produces residual material, which is referred to as tailings. In the tailing storage facility, there are several potentials for the emergence of heavy metal minerals. Rare earth elements are immobile, so the presence of these elements can be used as fingerprint elements or trace elements of geochemical distribution. The presence of rare earth elements in gold mining tailings is found in one of the gold mines located in Sambas Regency, South Kalimantan Province, but has not been exploited because of its uneconomical presence. In this study, to see the geochemical distribution of heavy metal elements and to examine the possibility of rare earth elements found around the tailings storage facility, 20 soil samples were taken which were then tested to X-Ray Diffraction (XRD) test to see the distribution of minerals, and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) to see elements in ppm units. The mineral content that dominates the research area is quartz with a concentration of 64.3%, clay minerals such as kaolinite, gibbsite, and dickite have the next mineral abundance. The presence of kaolinite minerals also indicates a positive relationship with the value of r: 0.539 between rare earth elements. Abundance of rare earth elements in the field strongly associated with the element Fe with correlation of 0.73. This indicates that Fe is an effective element for adsorption of immobile elements, one of which is rare earth elements. The elements Ce and La are the rare earth elements with the highest concentration, while the elements Lu and Tm have the lowest elemental concentrations. Based on the spider diagram, the concentration of rare earth elements at the research are LREE-rich type. Heavy metals with the highest abundance were found in the elements Mn, Cr, and Zn and Ag, Cu, and Ni had concentrations <5 ppm. Rare earth elements in this study has a moderate relationship with As and Cd, inversely to Cr, and doesn’t have a relationship with Zn, Ni, Cu, Cd and Mn. In general, the concentrations of rare earth elements and heavy metals were abundant in the tailings area and decreased radially with increasing distance from the tailings center. Except for Cr and Mn elements that are mobile are highly concentrated around the river.